Sperm Release From the Oviductal Epithelium Depends on Ca2+ Influx Upon Activation of CB1 and TRPV1 by Anandamide. Issue 2 (February 2016) - Gervasi, M.G.; Osycka‐Salut, C.; Sanchez, T.; Alonso, C.A.I.; Llados, C.; Castellano, L.; Franchi, A.M.; Villalón, M.; Perez‐Martinez, S.
ABSTRACT: The oviduct acts as a functional sperm reservoir in many mammalian species. Both binding and release of spermatozoa from the oviductal epithelium are mainly modulated by sperm capacitation. Several molecules from oviductal fluid are involved in the regulation of sperm function. Anandamide is a lipid mediator involved in reproductive physiology. Previously, we demonstrated that anandamide, through activation of the cannabinoid receptor type 1 (CB1), promotes sperm release from bovine oviductal epithelial cells, and through CB1 and the transient receptor potential vanilloid 1 (TRPV1), induces sperm capacitation. Herein we investigate co‐activation between CB1 and TRPV1, and Ca 2+ influx as part of the mechanism of action of anandamide during sperm release from oviductal cells. Our results indicate that in the absence of Ca 2+ anandamide failed to release spermatozoa from oviductal epithelial cells. Additionally, sperm release promoted by cannabinoid and vanilloid agonists was abolished when the spermatozoa were preloaded with BAPTA‐AM, a Ca 2+ chelator. We also determined Ca 2+ levels in spermatozoa preloaded with FURA2‐AM co‐cultured with oviductal cells and incubated with different cannabinoid and vanilloid agonists. The incubation with different agonists induced Ca 2+ influx, which was abolished by CB1 or TRPV1 antagonists. Our results also suggest that a phospholypase C (PLC) might mediate the activation of CB1 and TRPV1 in sperm release from the bovine oviduct. Therefore, our findings indicate that anandamide, through CB1 and TRPV1 activation, is involved in sperm release from the oviductal reservoir. An increase of sperm Ca 2+ levels and the PLC activation might be involved in anandamide signaling pathway. J. Cell. Biochem. 117: 320–333, 2016. © 2015 Wiley Periodicals, Inc.